Braid-reinforced PVDF hollow fiber membranes for high-efficiency separation of oily wastewater. Issue 2 (April 2022) - El-badawy, Tijjani; Othman, Mohd Hafiz Dzarfan; Adam, Mohd Ridhwan; Kamaludin, Roziana; Ismail, A.F.; Rahman, Mukhlis A.; Jaafar, Juhana; Rajabzadeh, Saeid; Matsuyama, Hideto; Usman, Jamilu; Kurniawan, Tonni Agustiono; Raji, Yusuf O.; et al.
Abstract: Several efforts to produce mechanically robust polymeric hollow fiber membranes have led to the use of polyethylene terephthalate (PET) hollow braided tubes, which offer rigidity to hollow fiber membranes. However, a compensation of flux exists with increased filtration pathway occasioned by braid substrate and thick polymer coating. It is often difficult to control the fabrication parameters to achieve uniformly coated and thin separation layer. In this work, we report a modification of the erstwhile dry-jet wet spinning process for braided hollow fiber by introducing a loop-system to increase resident time in the coagulation bath for effective solvent exchange and leaching of pore former additive. A combination of air gap (5, 15 and 25 cm), polymer concentration (15%, 17% and 19%) and take-up speed (1.2, 2.4 and 3.6 m/min) were varied to produce membranes with optimum filtration performance against crude oil emulsion feed. BRP-HM8 spun with 15 wt% PVDF, 15 cm air gap and take-up speed of 2 rpm exhibited thin and uniform coating outside of braid, well-developed pore structure resulting in high flux up to 620 L/m 2 h, good hydrophilic/oleophobic characteristics with > 98% rejection of crude oil as well high mechanical properties against harsh feed and elevated pressure. Graphical Abstract: ga1 Highlights: Loop-system for improved spinning of braided hollow fiber membranes. Thin and uniform polymer coating reducing filtration pathway with well-developed finger-like pores. Excellent rejection properties occasioned by good underwater oleophobicity. High-strength reusable membranes with simple flushing.